Application of Collaborative Learning Model Between Group Discussion and Practice to Improve Islamic Religious Education Learning Activities: Penerapan Model Pembelajaran Kolaborasi Antara Diskusi Kelompok dan Praktek untuk Meningkatkan Aktifitas Belajar Pendidikan Agama Islam - efnita efnita (International Journal of Technology Vocational Education and Training, 2021)
Classroom Action Research at UPT SMPN 2 Koto Baru with the aim of increasing the learning activities of Islamic Religious Education for Class VII A students in semester 1 of UPT SMPN 2 Koto Baru through group discussion and practice learning models. Learning has been carried out using a monotonous method with one-way lectures with the teacher as a techer center resulting in less developed student activities which in the end the learning outcomes are not in accordance with curriculum expectations. The research was carried out in two cycles and each cycle was carried out in two meetings. Every time a meeting, the learning process uses a discussion model and direct practice. As a data collection tool, student worksheets and sheets were used by the researcher as a direct observer with steps of action planning, action implementation, observation, evaluation and reflection for each cycle. Student learning outcomes have increased from the first cycle to the second cycle. Each student's practice value in each meeting has increased. The end of the first cycle to the second cycle has increased research activity obtained is an increase in learning outcomes 42.6% in the first cycle and increased in the second cycle to 66.28%. The number of students consists of 32 people consisting of 13 males and 19 females.